The diagnostic value of dual-phase cone-beam CT during hepatic arteriography in transarterial chemoembolization for hepatocellular carcinoma. Issue 12 (26th March 2021) - Higashihara, Hiroki; Osuga, Keigo; Onishi, Hiromitsu; Nakamoto, Atsushi; Tsuboyama, Takahiro; Tomiyama, Noriyuki
Abstract : Abstract: To evaluate the diagnostic value of dual-phase cone beam CT during hepatic arteriography (CBCTHA) for hepatocellular carcinoma (HCC). Thirty seven patients with unresectable HCC underwent the dual-phase CBCTHA prior to transarterial chemoembolization (TACE). Three blinded observers independently reviewed and compared the first phase CBCTHA images alone and the dual phase CBCTHA images. Diagnostic accuracy was evaluated by the alternative free-response receiver operating characteristic method (Area under the curve: Az value). Sensitivities were analyzed with the paired t test. The analysis was performed for overall HCCs, HCCs up to 1 cm and those larger than 1 cm. For all HCCs and HCCs up to 1 cm, Az value and sensitivity showed no significant difference between the first-phase CBCTHA alone and the dual-phase CBCTHA (Az: 0.81 vs 0.88, P  = .07, 0.79 and 0.85, P  = .14, sensitivity: 0.61 and 0.73, P  = .11, 0.41 and 0.52, P  = .33, respectively). For HCCs larger than 1 cm, the mean Az value and sensitivity for the dual-phase CBCTHA were significantly higher than those for the first phase CBCTHA alone (Az: 0.96 vs 0.92, P  = .008, sensitivity: 0.85 vs 0.75, P  = .013, respectively). The diagnostic accuracy of the dual-phase CBCTHA was superior to that of the first phase CBCTHA alone in the diagnosis of HCC larger than 1 cm.